Quality in marital relationship and self-esteem - Chong, Chin Yee (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study aims in studying the relationship between quality in marital relationship and self- esteem. In studying the relationship between quality in marital relationship and self-esteem, researcher make hypothesis to study the relationship between quality in marital relationship and self-esteem, the relationship between task accomplishment and self- esteem, the relationship between communication and self- esteem, and the relationship between affective expression and self-esteem.Spearman correlation Analysis Method was used to analysis the relationship between these variables. Besides studying the relationship between these variables, the researcher also looked at the differences of participants’ self-esteem base on selected demographic factor of gender. The difference in term of gender was analyzed using t-test. A survey research was conducted using questionnaires which we re selected from Dyadic Relationship Scale (2003) in Family Assessment Manual, version III and, Rosenberg Self-esteem Scale (1965). The Dyadic Relationship Scale was used to measure the relationship of the participants with their partner while the Rosenberg Self-esteem Scale was used to measure self-esteem of the participants. Task accomplishment, communication and affective expression are three of the seven subscales taken from Dyadic Relationship Scale in this study. By using purposive sampling method,75 out of 120 Christians from Grace Baptist Church Kuching were taken as the sample. The result shows that there is relationship between quality in relationship and self- esteem. The hypothesis of difference of the Christians’ self- esteem base on demographic factors was accepted. There is no difference of individuals’ self-esteem base on the demographic factor of gender. Communication in marital relationship is found to have no relationship with self-esteem. However, the researcher found that there is relationship between task accomplishment and self- esteem, and affective expression and self- esteem.This shows that task accomplishment and affective expression is an important element in marital relationship as they affect Christians’ self- esteem and Christian’s self-esteem might be affected by task accomplishment and affective expression in marital relationship.